The Influence of Autocratic Leadership Style And Work Conflict, On Employee Performance At CV. Tiga Putri Sukabumi - Wiwin Apriyanti; Dede Hertina (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
The purpose of this study was to determine the autocratic leadership style, work conflict, and employee performance at CV Tiga Putri Sukabumi, and to determine the effect of autocratic leadership style and work conflict on employee performance at CV Tiga Putri Sukabumi. The research method used is descriptive and verification. The population used are employees of the production section of CV. Three Putri Sukabumi with a sample of 60 respondents. The data analysis technique used is multiple linear regression and hypothesis testing. The result of this research is that the autocratic leadership style applied to CV Tiga Putri Sukabumi is considered less good. Work conflict at CV Tiga Putri Sukabumi is considered high and employee performance at CV Tiga Putri Sukabumi is still considered not high enough. Leadership style and work conflict simultaneously or partially have a significant effect on employee performance at CV Tiga Putri Sukabumi.